THE STRONG STATE: A STATISTICAL MEASUREMENT - O. F. Volochaeva; Y. Y. Belevskaya (Современная наука и инновации)
The article is devoted to estimating the strength of the state, using quantifiable indicators amenable to mathematical accounting. The article made the preparation of integrated index of a strong state. The main indicators which are: territory, population, military capacity, moral power, economic power and power of state institutions.